Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Lê Quang Khải

\(\dfrac{2}{3}\)×x-\(\dfrac{2}{5}\)=\(\dfrac{1}{2}\)×x-\(\dfrac{1}{3}\)

Nguyễn Lê Phước Thịnh
18 tháng 9 2024 lúc 21:00

\(\dfrac{2}{3}x-\dfrac{2}{5}=\dfrac{1}{2}x-\dfrac{1}{3}\)

=>\(\dfrac{2}{3}x-\dfrac{1}{2}x=-\dfrac{1}{3}+\dfrac{2}{5}\)

=>\(\dfrac{1}{6}x=-\dfrac{5}{15}+\dfrac{6}{15}=\dfrac{1}{15}\)

=>\(x=\dfrac{1}{15}:\dfrac{1}{6}=\dfrac{6}{15}=\dfrac{2}{5}\)


Các câu hỏi tương tự
Minahana
Xem chi tiết
Nguyễn Gia BảoB
Xem chi tiết
Lê Phương Linh
Xem chi tiết
Lê Phương Linh
Xem chi tiết
Lê Phương Linh
Xem chi tiết
Mthu
Xem chi tiết
-Eryy...-
Xem chi tiết
Lê Phương Linh
Xem chi tiết
juilya
Xem chi tiết
Lê Phương Linh
Xem chi tiết